Russian Orthodox Church and the Concept of War in Preaching Traditions (the Early 18th Century) - Liudmila Tretiakova; Liliya Beloglazova; Yuliya Yurova; Irina Shabaeva (Codrul Cosminului, 2020)
The paper describes the use of the concept of war in the works of the Russian Orthodox Church preachers using its imaginative and valuable characteristics. The authors reveal the essence and role of this concept in the Russian language culture in the context of ecclesiastical journalism of the early 18th century. Particular attention is paid to artistic means. The preachers used them to express their views on the events of the Great Northern War. The paper provides extensive coverage of the use of church propaganda to justify the causes of hostilities following the official position of the Russian government.